IGA binding lectins isolated from distinct artocarpus species demonstrate differential specificity - Hashim, Onn Haji; Ng, C.L.; Gendeh, G.S.; Jaafar, M.I.N. (1991)
The discovery of jacalin, a group of lectins from jackfruit seeds (Artocarpus heterophyllus), has attracted considerable attention due to its numerous interesting immunological properties as well as its usefulness in the isolation of various serum proteins. We have further identified a similar lectin from the seeds of Champedak (Artocarpus integer) which we refer to as lectin-C and performed comparative studies with two types of jacalin isolated from different batches of the Malaysian jackfruit seeds (jacalin-M1 and jacalin-M2). The three purified lectins demonstrated equivalent apparent M(r) of about 52,500, each of which comprised of a combination of two types of non-covalently-linked subunits with apparent M(r) of approximately 13,300 and 16,000. The lectins demonstrated equal haemagglutinating activity against human erythrocytes of blood groups A, B, AB and O. Our data also demonstrated that lectin-C, jacalin-M1 and jacalin-M2 are similar by selectively precipitating human serum IgA1 and colostral sIgA but not IgA2, IgD, IgG and IgM. When immunoelectrophoresis was performed on normal human sera and reacted with the lectins, single precipitin arcs corresponding to IgA immunoprecipitates were detected with lectin-C and jacalin-MI. Jacalin-M2, however, exhibited two closely associated precipitin arcs. The binding of these lectins with IgA was pronouncely inhibited in the presence of p-nitrophenyl-beta-D-galactopyranoside, 1-o-methyl-alpha-D-galactopyranoside, D-melibiose, N-acetyl-D-galactosamine and D-galactose. The data therefore provide evidence on the differential specificity of IgA binding lectins isolated from seeds of similar as well as distinct Artocarpus species.